A coating based on clove essential oils encapsulated by chitosan-myristic acid nanogel efficiently enhanced the shelf-life of beef cutlets. (December 2017) - Rajaei, Ahmad; Hadian, Mojgan; Mohsenifar, Afshin; Rahmani-Cherati, Tavoos; Tabatabaei, Meisam
Highlights: A coating based on clove EOs encapsulated by chitosan-myristic acid nanogel was developed. Enhanced antibacterial and antioxidant activity of CS-MA nanogel-encapsulated essential oils. Enhanced shelf-life of beef cutlets during refrigerated storage was achieved. The coating showed higher antibacterial activity against Salmonella enterica Ser. Enteritidis. Abstract: In the present study, a coating was investigated through the encapsulation of clove essential oils (CEOs) by chitosan (CS)–Myristic acid (MA) nanogel. The results of radical scavenging activity showed that the antioxidant activity of the CEOs was increased by encapsulation. Subsequently, the antibacterial activity of the coatings, i.e., free CEOs, CS–MA nanogel, and CS–MA nanogel encapsulated CEOs against Salmonella enteric Ser. Enteritidis was evaluated on inoculated beef samples. The results obtained showed that the CS–MA nanogel encapsulated CEOs was more effective compared with its free counterpart in controlling Salmonella population on beef under refrigerated storage. More specifically, the CS–MA nanogel encapsulated CEOs at only 2 mg/g beef was found promising in reducing S. enteric Ser. Enteritidis while it led to minimal unfavorable impacts on meat color values during prolonged storage. Overall, the findings achieved indicated that the encapsulation could considerably improve the performance of CEOs.